Detection and in vitro metabolism of the confiscated peptides BPC 157 and MGF R23H. Issue 10 (10th February 2017) - Cox, Holly D.; Miller, Geoff D.; Eichner, Daniel
Abstract : A new peptide, body protecting compound (BPC), BPC 157, and a variant of mechano‐growth factor (MGF), MGF R23H, were identified in confiscated vials. BPC 157 has the amino acid sequence, GEPPPGKPADDAGLV, and is currently under investigation for the promotion of healing and recovery in a variety of tissues. In vitro metabolism experiments in plasma demonstrate that MGF R23H has good stability and should be detectable in urine, while BPC 157 forms a stable metabolite that should be detectable in urine. A weak cation exchange solid phase extraction method was validated for detection of BPC 157 in urine. The method has a limit of detection of 0.1 ng/mL, precision of less than 20%, and good linearity, r 2 0.998. BPC 157 was stable in urine for at least 4 days. The specificity of the method is improved by measurement of a potential BPC metabolite along with the parent peptide. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The peptide BPC 157 was identified in confiscated vials and methods were developed for its detection in urine. The primary metabolite was identified and measured using in vitro methods.